2003
DOI: 10.3141/1856-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Truck Operating Characteristics on a Rural Interstate Freeway with Median Lane Truck Restriction

Abstract: The increase in truck traffic on interstate freeways continues to raise concerns about the large trucks’ dimensions that cause sight distance problems and about trucks’ low capability to accelerate, decelerate, and maintain speed particularly on steep grades. To address safety and operational concerns caused by truck traffic, a multitude of restriction policies have been instituted around the United States. This study was aimed at determining the operational and safety impacts of the 24-h restriction of trucks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For example, it was alleged that INGOs promoted homosexuality. 105 By defending LGBTQ rights and female reproductive rights, donors and INGOs reinforced these associations. 106 However, the centre-piece of this self-portrayed restoration was the revival of a project of national transformation.…”
Section: Dan Paget Democratizationmentioning
confidence: 99%
“…For example, it was alleged that INGOs promoted homosexuality. 105 By defending LGBTQ rights and female reproductive rights, donors and INGOs reinforced these associations. 106 However, the centre-piece of this self-portrayed restoration was the revival of a project of national transformation.…”
Section: Dan Paget Democratizationmentioning
confidence: 99%
“…They concluded that separating truck traffic from passenger cars for freeway facilities improves safety. Several other researchers have also stated the safety benefits of restriction of truck lane use (11)(12)(13)(14)(15).…”
Section: Crash Analysis and Traffic Characteristicsmentioning
confidence: 99%
“…Over the past decade, transportation researchers evaluated the effectiveness of truck lane restriction and differential speed limit strategies. While several studies evaluated the performance of such restrictions in terms of traffic operation (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), others focused on the safety impact of the restriction policies. The impacts of these regulatory practices on variables such as crash rate, lane distribution, average speed, density, and frequency of lane-changing maneuvers have been explored with statistical techniques such as empirical Bayes technique or with simulation models.…”
Section: Introductionmentioning
confidence: 99%
“…HOV lane restrictions only are found on some sections of I-95 and I-4. A review of operations on Florida's urban limited-access highways indicated that truck lane restrictions are currently in force 24 hours a day, but HOV lane restriction is relaxed during off-peak hours.The most common safety and operational benefits cited by many state agencies following the implementation of truck lane restrictions include reduced crashes, improved highway speeds, and improved safety in construction zones (2,(5)(6)(7). Furthermore, studies show that there are some psychological benefits of restricting trucks to certain lanes because passenger car drivers do feel intimidated and squeezed in when trucks are allowed to use all through lanes.…”
mentioning
confidence: 99%
“…The most common safety and operational benefits cited by many state agencies following the implementation of truck lane restrictions include reduced crashes, improved highway speeds, and improved safety in construction zones (2,(5)(6)(7). Furthermore, studies show that there are some psychological benefits of restricting trucks to certain lanes because passenger car drivers do feel intimidated and squeezed in when trucks are allowed to use all through lanes.…”
mentioning
confidence: 99%